RETRACTED ARTICLE: An Improved Human-Computer Interaction Content Recommendation Method Based on Knowledge Graph - He, Zhu (International journal of human-computer interaction, 2024)
We, the Editors and Publisher of International Journal of Human Computer Interaction, have retracted the following article: Zhu He (2023) An Improved Human-Computer Interaction Content Recommendation Method Based on Knowledge Graph, International Journal of Human Computer Interaction, DOI: 10.1080/10447318.2023.2295734 Following publication of the article, concerns were raised regarding significant overlap with the following article: Qiang He (2023) Human-computer interaction based on background knowledge and emotion certainty, PeerJ Computer Science 9:e1418, DOI: 10.7717/peerj-cs.1418 The author responded to our initial query but was unable to provide a satisfactory explanation for the significant level of overlap. As this is a breach of our editorial policies, we are retracting the article from the journal. The author was notified of this. We have been informed in our decision-making by our editorial policies and the COPE guidelines.